Quantum Mechanical Study of Some Biological Important Quorum Sensing Inhibitors in Different Solvent Media: Quantum Mechanical Study of Some Biological Important Quorum Sensing Inhibitors in Different Solvent Media - Das, Rajesh Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Quorum sensing (QS) is a phenomenon in which microcolonies get converted into a mature biofilm through different processes. Thus, by considering this communication system, it is possible to set up a useful new antimicrobial planning without the risk of growing resistance. The QS inhibition (QSI) process is completely safe for the environment and decreases the use of chemical. Keeping in view of this fact, the hamamelitanin (HAM) is one of the best QSIs, inhibiting the biofilm metabolic activity of all tested bacteria. In this study, molecular docking and in silico studies were performed to evaluate the drug likeliness behavior of some ester of gallic acid of D-hamamelose compounds as inhibitors of QS. The study comprised of 34 compounds belonging ester of gallic acid of D-hamamelose along with one standard QSI HAM. The molecular docking of some ester of gallic acid of D-hamamelose with 4g4k protein was performed by the AutoDock 1.5.6 suite. Molecular descriptor properties were evaluated by molinspiration and OSIRIS property explorer. The pharmacophore property has been generated by PharmaGist tools. Out of the 34 derivatives, 10 derivatives have qualified the standard value of the parameters World Drug Index (WDI), modern drug data report (MDDR), drug likeliness, drug score value and attach with the same fragment of protein just like by the natural ligand D-hamamelose or the standard QSI HAM. The binding energies of all the docked complex of compounds have larger negative values than that of HAM. The molecular docking study implied that the qualified compounds may use as a remarkable QSI. The pharmacophore study may be used to design and develop new drugs. This study notably supports a theoretical concept of these compounds as QSIs of Staphylococcus aureus